Staging Of Chronic Kidney Disease Among Elderly Patients: A Comparison Between Cystatin C And Creatinine Based Estimated Glomerular Filtration Rate - Khan, Irfan Ullah (2017)
Chronic kidney disease (CKD) is a major public health problem worldwide. Just like other parts of the world the prevalence of CKD is increasing in Malaysia (9.07% in 2011). In routine clinical practice serum creatinine (Scr) is the most widely used endogenous biomarker of renal function. However, literature review reveals that creatinine concentration has been affected by age, gender, muscle mass and diet, which may lead to over/under estimation of CKD. Cystatin C an endogenous biomarker produced by all the nucleated cells at a constant rate has been reported to be a more accurate kidney marker and better at estimating small changes in glomerular filtration (GFR). Therefore, the current cross-sectional study at HUSM was conducted with the aim to evaluate the sensitivity and specificity of cystatin C and creatinine based eGFR equations in staging CKD using Chronic Kidney Disease Epidemiology Collaboration combined (CKD-EPlcr-cys) equation as a reference. Furthermore, we also evaluated the concordance and predictors of concordance between Modification of diet in renal disease (MORD) and CKD-EPlcys equations in staging CKD. A total of 300 connectively enrolled established elderly CKD patients at the study site who met the eligibility criteria were included. Serum samples were collected and analyzed for serum creatinine and serum cystatin C. eGFR was calculated on the basis of CKD-EPlcr-cys, CKD-EPlcys, CKD-EPlcr and MDRD.